2023
DOI: 10.1038/s41598-023-49973-7
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-rich water: a key player in boosting wheat (Triticum aestivum L.) seedling growth and drought resilience

Md. Ariful Islam,
Most. Nourin Akther Shorna,
Shirmin Islam
et al.

Abstract: In the modern world, wheat, a vital global cereal and the second most consumed, is vulnerable to climate change impacts. These include erratic rainfall and extreme temperatures, endangering global food security. Research on hydrogen-rich water (HRW) has gained momentum in plant and agricultural sciences due to its diverse functions. This study examined the effects of different HRW treatment durations on wheat, revealing that the 4-h treatment had the highest germination rate, enhancing potential, vigor, and ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 65 publications
1
0
0
Order By: Relevance
“…Additionally, the impact of drought stress on wheat germination and growth, as seen in the notable RWC decline from the Early to Mid stages in our study, is corroborated by similar findings in other research [53]. On the other hand, our findings contrast with a study that found variable responses to PEG-induced drought stress among different bread wheat genotypes, suggesting there is no uniform response pattern across genotypes in the initial stages of stress [54]. This is complemented by another study [55], which shows that drought-tolerant wheat genotypes have developed more efficient adaptive strategies, such as deeper root systems and higher biomass, indicating a diverse range of drought responses extending beyond our initial observations.…”
Section: Changes In Relative Water Content (Rwc)supporting
confidence: 91%
“…Additionally, the impact of drought stress on wheat germination and growth, as seen in the notable RWC decline from the Early to Mid stages in our study, is corroborated by similar findings in other research [53]. On the other hand, our findings contrast with a study that found variable responses to PEG-induced drought stress among different bread wheat genotypes, suggesting there is no uniform response pattern across genotypes in the initial stages of stress [54]. This is complemented by another study [55], which shows that drought-tolerant wheat genotypes have developed more efficient adaptive strategies, such as deeper root systems and higher biomass, indicating a diverse range of drought responses extending beyond our initial observations.…”
Section: Changes In Relative Water Content (Rwc)supporting
confidence: 91%